Effect of air pollution on health care expenditure: Evidence from respiratory diseases - Liu, Ya‐Ming; Ao, Chon‐Kit (Health economics, 2021)
Recent reports show that at least 95% of the world's population is breathing polluted air. However, the impact of air quality on air pollution‐related medical expenditure and utilization is sparse. This study estimates the short‐term health care cost impacts of air pollution using a meteorological phenomenon—thermal inversion—as an instrumental variable for air quality. Using information on outpatient care for respiratory diseases from universal health insurance claim data in Taiwan during 2006–2012, our estimates suggest that a one‐unit reduction in the air quality index (AQI) leads to NT$2.3 billion (nearly US$74 million) of savings in respiratory‐related outpatient expenditure per year. Given that the average AQI is equal to 32 during our study period, completely removing air pollution would reduce the national health expenditure by approximately 8% annually. Our results provide the important implication that the cost of controlling air pollutant emissions can be offset by curtailing health care expenditure.